Bioinformatic prediction of putative metallothioneins in non-ciliate protists. (13th April 2022) - Balzano, Sergio; Sardo, Angela
Abstract : Intracellular ligands that bind heavy metals (HMs) and thereby minimize their detrimental effects to cellular metabolism are attracting great interest for a number of applications including bioremediation and development of HM-biosensors. Metallothioneins (MTs) are short, cysteine-rich, genetically encoded proteins involved in intracellular metal-binding and play a key role in detoxification of HMs. We searched approximately 700 genomes and transcriptomes of non-ciliate protists for novel putative MTs by similarity and structural analyses and found 21 unique proteins playing a potential role as MTs. Most putative MTs derive from heterokonts and dinoflagellates and share common features such as (i) a putative metal-binding domain in proximity of the N-terminus, (ii) two putative MT-specific domains near the C-terminus and (iii) one to three CTCGXXCXCGXXCXCXXC patterns. Although the biological function of these proteins has not been experimentally proven, knowledge of their genetic sequences adds useful information on proteins that are potentially involved in HM-binding and can contribute to the design of future biomolecular assays on HM–microbe interactions and MT-based biosensors.